Development on Indigenous Homelands and the Need to Get Back to Basics with Scoping: Is there Still "Unceded" Land in Northern Ontario, Canada, with Respect to Treaty No. 9 and its Adhesions? - Tsuji, Leonard; Tsuji, Stephen (The International Indigenous Policy Journal, 2021)
Scoping includes the establishment of unambiguous spatial boundaries for a proposed development project (e.g., a treaty) and is especially important with respect to development on Indigenous homelands. Improper scoping leads to a flawed product, such as a flawed treaty or environmental impact assessment, by excluding stakeholders from the process. A comprehensive literature search was conducted to gather (and collate) printed and online material in relation to Treaty No. 9 and its Adhesions, as well as the Line-AB. We searched academic databases as well as the Library and Archives Canada. The examination of Treaty No. 9 and its Adhesions revealed that there is unceded land in each of four separate scenarios, which are related to the Line-AB and/or emergent land in Northern Ontario, Canada. Lastly, we present lessons learned from our case study. However, since each development initiative and each Indigenous Nation is unique, these suggestions should be taken as a bare minimum or starting point for the scoping process in relation to development projects on Indigenous homelands.